2004
DOI: 10.1038/sj.onc.1207817
|View full text |Cite
|
Sign up to set email alerts
|

MAGI-3 is involved in the regulation of the JNK signaling pathway as a scaffold protein for frizzled and Ltap

Abstract: A seven-transmembrane protein, frizzled, has been implicated in a planar cell polarity (PCP) pathway as well as the canonical Wnt signaling pathway. Although both pathways require a cytoplasmic protein, dishevelled, the molecular mechanism by which frizzled regulates intracellular signaling remains to be elucidated. In the mouse, nine frizzled family members have been identified and six of them contain a PDZ-binding motif at their carboxyltermini. In this study, we show that a multi-PDZ containing protein, MAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 41 publications
1
58
0
1
Order By: Relevance
“…A previous paper showed that MAGI-3 (membrane-associated guanylate cyclase with inverted orientation-3) could function as a scaffold protein for Fz4 and Vangl2 to regulate the c-Jun N-terminal protein kinase cascade. However, whereas the authors identified a direct interaction between MAGI-3 and Fz4 or Fz7, no interaction was demonstrated between MAGI-3 and Fz3 or Fz6 nor between Fz4 and Vangl2 (Yao et al, 2004).…”
Section: Fz3 Is Asymmetrically Localized and Interacts With Vangl2mentioning
confidence: 80%
“…A previous paper showed that MAGI-3 (membrane-associated guanylate cyclase with inverted orientation-3) could function as a scaffold protein for Fz4 and Vangl2 to regulate the c-Jun N-terminal protein kinase cascade. However, whereas the authors identified a direct interaction between MAGI-3 and Fz4 or Fz7, no interaction was demonstrated between MAGI-3 and Fz3 or Fz6 nor between Fz4 and Vangl2 (Yao et al, 2004).…”
Section: Fz3 Is Asymmetrically Localized and Interacts With Vangl2mentioning
confidence: 80%
“…A further question to address is, whether MAGI1 could itself be downregulated by Wnt signaling in CRC cells, thereby creating a self-sustaining loop much alike COX-2, which is both a Wnt-activating protein and a Wnt target gene (Araki et al, 2003;Buchanan and DuBois, 2006). Interestingly, MAGI3 was shown to bind to the Wnt receptors Frizzled-4 and Frizzled-7 (Yao et al, 2004), and to Ltap, a protein homologous to Stbm, which genetically interacts with frizzled to regulate Wnt signaling in Drosophila (Taylor et al, 1998;Wolff and Rubin, 1998). In epithelial cells, MAGI3 and Frizzled-4 form a complex that localizes at cell contact sites (Yao et al, 2004).…”
Section: Magi1 As a Coxib-induced Tumor-suppressor Protein In Crc Celmentioning
confidence: 99%
“…Interestingly, MAGI3 was shown to bind to the Wnt receptors Frizzled-4 and Frizzled-7 (Yao et al, 2004), and to Ltap, a protein homologous to Stbm, which genetically interacts with frizzled to regulate Wnt signaling in Drosophila (Taylor et al, 1998;Wolff and Rubin, 1998). In epithelial cells, MAGI3 and Frizzled-4 form a complex that localizes at cell contact sites (Yao et al, 2004). Taken together, these observations suggest that MAGI1 may be a physiological regulator of Wnt signaling.…”
Section: Magi1 As a Coxib-induced Tumor-suppressor Protein In Crc Celmentioning
confidence: 99%
“…Pro-IL-16 is an abundant protein constitutively expressed in human peripheral blood T cells that can induce cell growth arrest. MAGI-3 belongs to the same MAGUK family as hDlg and has been implicated in several cellular signaling pathways involved in cell survival as well as cell polarity (Wu et al, 2000;Adamsky et al, 2003;Wilson et al, 2003;Ohashi et al, 2004;Yao et al, 2004).…”
Section: Role Of Tax-1 C-terminus In Transformationmentioning
confidence: 99%